The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5858/arpa.2012-0704-oa
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of H3K9me3 Is a Strong Predictor of Poor Survival in Patients With Salivary Adenoid Cystic Carcinoma

Abstract: Context.—Histone methylation and acetylation play important roles in the carcinogenesis and progression of cancer. Objective.—To investigate whether histone modifications influence the prognosis of patients with salivary adenoid cystic carcinoma (ACC). Design.—The expression of histone H3 lysine 9 trimethylation (H3K9me3) and histone H3 lysine 9 acetylation (H3K9Ac) was assessed by immunohistochemistry in 66 specimens of primary ACC. Tests were used to determine the presence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 35 publications
1
39
0
3
Order By: Relevance
“…For example, the specific genetic features of a cancer in an individual also may have prognostic value. A higher expression of H3K9me3 is correlated with an increased probability of DM ( p = 0.001) in adenoid cystic carcinoma, 13 but also, a higher expression of TMPRSS4 was associated with a higher tendency toward both lymph node metastasis ( p = 0.002) and distant metastasis in ( p < 0.001) in adenoid cystic carcinoma. 14 In one study of salivary duct cancer, p53 expression correlated with local disease recurrence ( p < 0.013), distant metastasis ( p < 0.049), and 5-year survival ( p < 0.008), and HER-2/ neu overexpression correlated with both distant metastasis ( p < 0.034) and 5-year survival ( p < 0.0239).…”
Section: Discussionmentioning
confidence: 94%
“…For example, the specific genetic features of a cancer in an individual also may have prognostic value. A higher expression of H3K9me3 is correlated with an increased probability of DM ( p = 0.001) in adenoid cystic carcinoma, 13 but also, a higher expression of TMPRSS4 was associated with a higher tendency toward both lymph node metastasis ( p = 0.002) and distant metastasis in ( p < 0.001) in adenoid cystic carcinoma. 14 In one study of salivary duct cancer, p53 expression correlated with local disease recurrence ( p < 0.013), distant metastasis ( p < 0.049), and 5-year survival ( p < 0.008), and HER-2/ neu overexpression correlated with both distant metastasis ( p < 0.034) and 5-year survival ( p < 0.0239).…”
Section: Discussionmentioning
confidence: 94%
“…21,22 Our previous studies also showed that molecular markers such as H3K9me3 expression can be used as indicators for predicting the prognosis for ACC patients. 15 However, it was not clear which genes were regulated by H3K9me3 to influence tumor characteristics. Building on the results of previous studies, this study further analyzed whether H3K9me3 influenced the biologic behavior of ACC tumors through the silencing of tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…It remains difficult for clinicians to select appropriate treatment strategies and make prognoses for these patients. Many additional clinicopathologic and biologic markers have been investigated for predicting outcomes and supplementing the TNM classifications …”
Section: Introductionmentioning
confidence: 99%
“…Many additional clinicopathologic and biologic markers have been investigated for predicting outcomes and supplementing the TNM classifications. [4][5][6][7] The 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT provides useful functional and anatomic information and plays a major role in the management of patients affected by head and neck cancer. 8 It is indicated for staging, especially to evaluate lymph nodes and distant metastases involvement in stage III and IV disease, to discriminate between unilateral and bilateral lymph node involvement, and to detect synchronous primaries, with consequent impact on treatment selection in a significant number of patients.…”
Section: Introductionmentioning
confidence: 99%